Synthesis, Structure, and Magnetic Properties of Phosphinate‐Bridged Hexanuclear FeIII Complexes Containing Two Butterfly‐Shaped Fe3O Cores. Issue 34 (December 2015) - Goura, Joydeb; Oyarzabal, Itziar; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract: Invited for the cover of this issue are Enrique Colacio from the University of Granada, Spain, and Vadapalli Chandrasekhar from the Indian Institute of Technology, Kanpur, India. The cover image shows the two hexanuclear Fe III phosphinate clusters, whose magnetic properties were investigated, against a background of butterflies, which delineate the structure of the cores. Abstract : The interesting magnetochemistry of these complexes resulting from the triangular topology of the Fe3O subunits gives rise to competing antiferromagnetic interactions and spin frustration... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 5601 ff .